Describing and understanding the enacted curriculum of selected Grade 10 Life Science teachers in the Western Cape, South Africa - Petersen, Andrew John (School of Education, 2018)
This study was conducted in a school in the Western Cape, South Africa situated in a community where learners came from difficult social backgrounds. Previous research has alluded to the challenges faced by teachers equipped with inadequate skills and a lack of effective modelling or mentoring to implement a formal curriculum that is outcomes-based and learner centred. The focus of the study was to uncover the enacted curriculum (and the underlying reasons for the enactment) of four Grade 10 Life Sciences Teachers. This multiple case study is based on data collection strategies that included video and audio-transcripts of the lessons as well as the use of additional relevant documents such as, for example, notes from lesson observations, and learner notebooks. These data were coded using NUDIST and then further analysed using the Pedagogic Content Knowledge (PCK) evidence-reporting table (PCK ERT). Interviews were conducted before the teaching events to allow for content representations (CoRes) to be developed. Overall the teachers lacked planning and the habit of reflection in and of practice. Hence video-stimulated interviews conducted after the teaching events allowed for Pedagogical and Professional experience Repertoires (PaP-eRs) to be developed in order to describe (from a teachers' perspective) what teachers did and why they did what they did. Teachers had varying backgrounds and experience and displayed very individualised and different enactments of the curriculum but they all used a consistent didactic approach in their teaching. The absence of teacher efficacy and the lack of integration of the PCK components limited the transformation of the content in any meaningful way and hence resulted in weak PCK. The relevance of PCK ERT as a descriptive framework for PCK in the context of this research is questioned on epistemic grounds. Factors identified that constrained the enacted practices of teachers included teachers' belief, orientation, poor Subject Matter Knowledge (SMK), school context and their perceptions of learners.